A CIDADE DO RIO DE JANEIRO E A ARTICULAÇÃO DA REGIÃO EM TORNO DO ATLÂNTICO-SUL: SÉCULOS XVII E XVIII (Revista de História Regional, 2007)
Along the XVII century, based on settled economic interests in Rio de Janeiro, the supremacy of its harbour was asserted, not only inside the middle South of Portuguese America but in the whole extension of Subequatorial Atlantic. The discovery of gold in the interior of Minas Gerais reinforced its commercial and marine status, giving it great importance and centricity inside the colony and within the colonial empire. By attracting the metropolitan fiscal, military, administrative and commercial apparatus, the city of Rio de Janeiro would become a target, not only of Portuguese shipping but also of other European potencies, what would represent continuous menaces to its integrity and conservation. The present article aims at an analysis of the metropolitan politics, keeping the defence and the safety of the city of Rio de Janeiro, relating it to the surrounded territories and building up an specific area inside the Portuguese colonial domains in South Atlantic.